2023
DOI: 10.1002/ange.202303124
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Methanol‐to‐Gasoline Process Over Zeolite Beta

Abstract: Decarbonizing the transportation sector is among the biggest challenges in the fight against climate change. CO2‐neutral fuels, such as those obtained from renewable methanol, have the potential to account for a large share of the solution, since these could be directly compatible with existing power trains. Although discovered in 1977, the zeolite‐catalyzed methanol‐to‐gasoline (MTG) process has hardly reached industrial maturity, among other reasons, because maximizing the production of gasoline range hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This observation reveals the descriptor role of HMB + species during the reaction, which was previously reported to be an essential hydrocarbon pool (HCP) species during the MTH process over the zeolite *BEA. [61,68,76] The similar nature of 12MR pore in both MTW and *BEA endows IZC-7, 9, and 13 the analogous reaction patterns. The non-identical spectral pattern of IZC-16 material implies its different framework structures (possibly due to the existence of mixed-phase), which led to other preferential HCP species forming during the catalysis.…”
Section: Operando Uv-vis Drs and Online Ms Studymentioning
confidence: 93%
See 2 more Smart Citations
“…This observation reveals the descriptor role of HMB + species during the reaction, which was previously reported to be an essential hydrocarbon pool (HCP) species during the MTH process over the zeolite *BEA. [61,68,76] The similar nature of 12MR pore in both MTW and *BEA endows IZC-7, 9, and 13 the analogous reaction patterns. The non-identical spectral pattern of IZC-16 material implies its different framework structures (possibly due to the existence of mixed-phase), which led to other preferential HCP species forming during the catalysis.…”
Section: Operando Uv-vis Drs and Online Ms Studymentioning
confidence: 93%
“…Not only the acidity features, the zeolite topology (especially mixed phases in IZC-16), pore system, and particle size would collectively impact the catalytic performance in the current study (vide supra). The zeolite *BEA (3D) should be worth mentioning for being prone to make gasoline-ranged hydrocarbons during the MTH process, [46,60,61] while zeolite MTW (1D) has been shown to exhibit a preference for C 4 + products. [45,62] The hydrocarbon selectivity analysis in Figure 3 revealed that the C 4 -C 7 (gasoline-ranged) paraffins accounted for 40-60 % of all catalysts before the deactivation.…”
Section: Synthesis and Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation